Thermal‒hydraulic‒mechanical‒chemical coupling analysis of enhanced geothermal systems based on an embedded discrete fracture model - Han, Dongxu; Zhang, Weitao; Jiao, Kaituo; Yu, Bo; Li, Tingyu; Gong, Liang; Wang, Shurong (Natural Gas Industry B, 2023)
Enhanced geothermal system (EGS) is subject to the comprehensive effects of multiple physical fields during the long-term heat extraction process, including hydraulic (H), thermal (T), mechanical (M) and chemical (C) fields. The embedded discrete fracture model (EDFM) can effectively simulate the variations of flow, temperature, mechanical and concentration fields in fractured reservoirs. At present, however, the thermo-hydro-mechanical-chemical (THMC) coupling model based on EDFM is less researched. In this paper, the THMC coupling model of fractured reservoir is established based on EDFM by considering the changes in reservoir heterogeneity and physical properties as well as water–rock reactions. Then, the spatiotemporal evolution of flow, temperature, displacement and concentration fields in the operation process of EGS is simulated and analyzed. And the following research results are obtained. First, when the permeability of the basement rock is low, the production temperature decrease during exploitation is gradual, allowing EGS to maintain a high exploitation temperature for an extended period. However, lower permeability may result in a decrease in the quality flow rate from production wells, thereby affecting net heat extraction power. Second, when fracture permeability or fracture opening changes, EGS can output higher temperature stably for a certain period and then the temperature decreases at different amplitudes. When the fracture permeability increases to a certain value or the fracture opening decreases to a certain value, the influence of the change in fracture parameters on production temperature gets weak. Third, After 40 years of EGS operation, considering variable property fluids results in a 22 °C lower exploitation temperature compared to using constant property fluids, and considering water–rock reactions results in a 15 °C lower exploitation temperature, with a 12.5 % increase in reservoir average porosity. In conclusion, when researching a long-term operating EGS, it is necessary to comprehensively consider the influences of reservoir rock parameters, physical properties of injected fluid, water–rock reaction and other factors. And in the future, attention shall be paid to the two-way coupling of chemical reaction and mechanical deformation of other mineral compositions in the reservoir to the hydro-thermo-chemical field influence, so as to provide more accurate and reliable prediction for the engineering development and utilization of EGS reservoirs.